Asia desde la academia Sudamericana - Carranco Paredes, Santiago (2018)
The idea that Asia and the studies of this continent should have a great preeminence for the South American and Northwestern academies has become a cliché. Several studies has confirmed the preponderance of Asian states for the understanding of current commercial, social, political, economic and academic relations. The present study is not going to worry about showing the expansion of the Asian influence within the South American academy, rather, it will be limited to review the way in which the South American universities are studying Southeast Asia through a quantitative study that perceived as main variables, the subjects that study Asia in the region, their contents and the universities that dictate them.